Respuesta :

ANSWER

[tex]3\le x\le6[/tex]

EXPLANATION

The given inequality is

[tex] {x}^{2} - 9x + 18 \leqslant 0[/tex]

This is the same as

[tex](x - 3)(x - 6) \leqslant 0[/tex]

The corresponding equation is

[tex](x - 3)(x - 6)= 0[/tex]

By the zero product principle,

[tex]x = 3 \: or \: x = 6[/tex]

We now plot the boundaries and test for the region that satisfies the inequality.

See attachment.

From the graph the solution is

[tex]3\le x\le6[/tex]

Ver imagen kudzordzifrancis
ACCESS MORE